UNMANAGEABLE RESPONSIBILITY? GENDERED PERCEPTIONS OF PARENT CARE AMONG ADULT CHILDREN AT WORKING AGE IN JAPAN - Hirayama, R (Innov Aging, 2018)
Our aim in this study was to explore whether and how Japanese adult children’s perceived manageability of caregiving to older parents was influenced by their work and family circumstances. With a rapid increase in older population under the familistic elder care system, Japanese adult children at working age are increasingly likely to be called upon to meet parental care needs. Yet, little is known about what can make these adult children well prepared to manage parent caregiving. Using online survey data from adult daughters (n = 526) and sons (n = 474) who were all employees with no parent care experiences ever, we examined what made a difference in their perceived manageability of parental caregiving. In doing so, we focused on their employment as well as marital status, both of which were, on the basis of extant literature, hypothesized to be a key influence over adult children’s views of parent care. Our outcomes of interest were perceived manageability of five different care tasks (e.g., hands-on care, help with housework), and we regressed participants’ perceived manageability of each task on their employment and marital status, which was conducted for daughters and for sons separately but simultaneously (i.e., multiple group analysis). Results indicated that, for daughters, neither employment nor marital status made a difference, whereas sons in regular employment, particularly those with spouse, were lower in perceived manageability of any care tasks. We discuss these results in relation to the male breadwinner model that is deep-seated in Japan’s societal systems.